Inventory of Diseases in Red Shallot Plants (Allium ascalonicum) - Haryuni, Haryuni; Setyadi, Ardhanesdian Rizqi; Suprapti, Endang; Dewi, Tyas Soemarah Kurnia; Irawan, Norbertus Citra; Rahman, Azhar Aditya (Biosaintifika: Journal of Biology & Biology Education, 2024)
Shallots (Allium ascalonicum) are a popular spice vegetable cultivated in Indonesia, ranging from lowlands to highlands. Their demand continues to grow as they are an essential kitchen commodity, although their prices often fluctuate. This research aimed to examine the disease symptoms in shallot plants caused by pathogenic fungi and to identify the types of pathogenic fungi present on agricultural land in Bangsalan Village, Boyolali Regency. The study consisted of three blocks, each containing 12 plots, and each plot comprising 15 plants. From each plot, five plants were randomly selected as samples. This qualitative research utilized observational and descriptive methods, where symptoms observed in the field were described and identified based on macroscopic and microscopic characteristics. Macroscopic identification revealed symptoms such as wilting, rot, and spots on both leaves and tubers. Microscopic identification confirmed infections by the fungi Colletotrichum sp. (causing anthracnose), Fusarium spp., and Aspergillus sp. on shallots. The findings from this study provide valuable recommendations for managing shallot diseases in subsequent planting seasons if similar symptoms are observed.